ANALISIS PERMEABILITAS LAPISAN TANAH ATAS DI BERBAGAI SATUAN LAHAN DI SUBDAS BINUANG, KALIMANTAN SELATAN - Efrinda Ayuningtyas (Institute of Computer Science (IOCS), 2023)
Binuang Sub-watershed is a small watershed in the Barito River Basin, near the Meratus Mountains, South Kalimantan. The opening and transformation of land in the framework of the expansion of coal mining zones is a problem of environmental stability in this region. The need to analyze the permeability coefficient is the initial stage carried out in this study, which will later become the basis for determining the appropriate type of land protection. Soil sampling is carried out on the top layer of soil with a depth of 0-30 cm. Testing of physical properties of the soil is carried out in the laboratory with the help of several analyzes, namely: soil texture, volume weight and soil density, soil porosity and soil permeability. The number of soil samples as many as 16 samples, each representing one unit of land in the entire Binuang Sub-watershed. The results showed that the soil texture, bulk density and soil porosity affect the degree of soil permeability. The highest level of soil permeability was observed in kc4, SB2 and LB6 land units. The permeability coefficient in three land units is influenced by the high content of sand fractions in the soil structure, so the porosity of the soil is also higher. This study assesses the relationship between the physical properties of soil that became the basis for further research, especially with regard to the level of suitability of land for agriculture and land degradation.